An evaluation of a third-party logistics provider: The application of the rough Dombi-Hamy mean operator - Sinani, Feta; Erceg, Zivko; Vasiljević, Marko (Decision Making: Applications in Management and Engineering, 2020)
Third-party logistics (3PL) has involved a significant response among researchers and practitioners in the recent decade. In the global competitive scenario, multinational companies (MNCs) not only improve the quality of the service and increase efficiency, but they also decrease costs by means of 3PL. However, the assessment and selection of 3PL is a very critical decision to make, comprising intricacy due to the existence of various imprecisely based criteria. Also, uncertainty is an unavoidable part of information in the decision-making process and its importance in the selection process is relatively high and needs to be carefully considered. Consequently, incomplete and inadequate data or information may occur among other various selection criteria, which can be termed as a multi-criteria decision-making (MCDM) problem. Rough numbers are very flexible to model this type of uncertainty occurring in MCDM problems. In this paper, the Hamy Mean (HM) operator and Dombi operations are expanded by rough numbers (RNs) so as to propose the Rough Number Dombi-Hamy Mean (RNDHM) operator. Then, the Multi-Attribute Decision-Making (MADM) model is designed with the RNDHM operator. Finally, the RNDHM is employed to achieve the final ranking of the 3PL providers.